Pedagogical imagination and practical wisdom: the role of success-narratives in teacher education and professional development. Issue 4 (3rd July 2016) - Tyson, Ruhi
Abstract: There is an increasing awareness that teaching is a practice where moral action is inseparable from pedagogical action, and where wise deliberation or reflection on what course of action to take as an educator is an important part of being a good teacher. This article focuses on rethinking the role of narratives as an articulation of such practical knowledge and the enrichment they might bring to a teacher's pedagogical imagination. Working within a conceptual framework drawing on Schön and Aristotle, the study presents a group of narratives describing successful conflict resolution told by students at a newly launched teacher education program. These are discussed as part of a teachers practice repertoire and the argument is made that the local and personal repertoires of practitioners need to be complemented with elements from the repertoire of others, something systematic research into narratives of teaching in action can be part of.